L’expertise CHSCT : engagement ou indépendance ? Quelques réflexions autour du positionnement et du rôle de l’expertise CHSCT - Nicolas Spire (La Nouvelle Revue du Travail)
Working as a consultant for a specialist health and safety committee firm, the author seeks to analyse the recent (but still nascent) development of health and safety committee expertise, portrayed here as a new kind of union tool. Based on his personal experience, he questions the conditions under which these singular actions are being developed and carried out. Requested by staff representatives, they are funded by employers and only occur in case of ministerial approval. The article starts by presenting an analysis of the field – in the Bourdieusian sense of the term – represented nowadays by the variety of health and safety committee consultancies. It then seeks to identify the profile of actors serving a dual role as order givers and order takers: elected and union officials seeking this kind of expertise, belonging to parties acting within the world of work but also on its margins. Lastly, he looks at the usefulness – hence the future – of such actions, which despite their singularity have had the effect of renewing both union activity and the balance of power within companies.